Modelling the surface circulation and thermal structure of a tropical reservoir using three-dimensional hydrodynamic lake model and remote-sensing data - Curtarelli, Marcelo Pedroso; Alcantara, Enner [UNESP]; Renno, Camilo Daleles; Assireu, Arcilan Trevenzoli; Bonnet, Marie Paule; Stech, Jose Luiz (Wiley-Blackwell, 2014)
Diurnal variations in surface circulation, heat budget and thermal structure were investigated in a tropical reservoir using a synergistic approach that combines in situ observations, remote-sensing data and numerical modelling. The study area, the Itumbiara Reservoir (Brazil) at the beginning of the austral winter, is characterized by the presence of a weak thermal stratification and the passage of several cold fronts. Both in situ observations and numerical modelling showed that the surface circulation is wind-driven. The strongest water current was observed at 13:00h, which lagged behind the strongest wind. The daily heat budget was negative during the period and was controlled by short-wave radiation and latent heat flux. The diurnal cycle of stratification was at its maximum at 17:00h, and the surface mixed layer deepens at night. The colder waters of the Paranaiba River contribute to the stability of the water column near the river-reservoir transition zone.
Keywords: dam; environmental management; reservoir; simulation modelling